Experimental investigation on the erosion characteristics of high pressure cavitation jet - Toh, Boon Loong (Nanyang Technological University, 2020)
Knowledge on the erosional characteristics of a high pressure cavitation jet enables advancement on future external surface finishing techniques. For example, understanding the parameters to produce a cavitating jet with large finishing area and cavitation intensity is essential to perform good surface finishing. This paper presents the approach of using a cavitating jet to perform external surface finishing on additive manufactured components. Subsequent analysis on the surface finished component will aid in the understanding of the cavitating jet erosional characteristics. Experiments are performed on a square surface of Inconel 625 component manufactured using Direct Metal Laser Sintering (DMLS) technique. Cavitation erosion performed for this investigation resulted in up to 45% reduction in average surface roughness (Sa). Images from the Laser Scanning Microscope and Scanning Electron Microscope showed that erosion due to a cavitating jet can remove surface irregularities and smoothen uneven surfaces.